Capital inflow into developing economies: A macroeconomic study - Soumyen Sikdar (Osaka University, Institute of Social and Economic Research (ISER), 2008)
External capital inflow on a massive scale into the emerging market economies is a very significant phenomenon of recent years. Making distinctions between direct investment, real and financial, and portfolio investment and incorporating crowding in or crowding out effects we derive some results about the impact of higher inflow on output, investment and the exchange rare. A formula is suggested for estimating the cost of central bank intervention.
Keywords: E12; F32; F41; 330; Foreign direct investment; Foreign portfolio investment; Foreign reserves; Flexible exchange rate